1995
DOI: 10.1161/01.cir.92.6.1422
|View full text |Cite
|
Sign up to set email alerts
|

Insulin, Intact and Split Proinsulin, and Coronary Artery Disease in Young Men

Abstract: This study shows that young, nondiabetic, male survivors of myocardial infarction are truly hyperinsulinemic during an OGTT and suggests a close association between proinsulin and coronary atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 29 publications
3
61
1
1
Order By: Relevance
“…Many studies have shown a relationship between proinsulin, proinsulin split products, and atherosclerotic lesions, but they were all cross-sectional studies, and the majority of them included only men [1,5,22]. In a crosssectional analysis of 1,456 nondiabetic participants in the Rancho Bernardo Study, proinsulin was positively associated with prevalent CHD in men and women [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have shown a relationship between proinsulin, proinsulin split products, and atherosclerotic lesions, but they were all cross-sectional studies, and the majority of them included only men [1,5,22]. In a crosssectional analysis of 1,456 nondiabetic participants in the Rancho Bernardo Study, proinsulin was positively associated with prevalent CHD in men and women [23].…”
Section: Discussionmentioning
confidence: 99%
“…When we corrected statistically for the non-fasting condition or linearly for hours since last meal intake, the results did not change substantially. Furthermore, proinsulin may be a more reliable measure of beta cell activity due to its longer half-life and lower variability than specific insulin when assessed in plasma samples [5]. This may favour proinsulin compared with insulin in regression analyses, and proinsulin is probably better than insulin for estimating future risk for CVD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are numerous possible explanations for the observed relation of proinsulin and insulin resistance to the incidence of stroke/TIA. First, high plasma proinsulin concentrations are associated with coronary artery atherosclerosis [13] and with an increased intima-media thickness in the common carotid artery [14]. In clinical trials greatly increased human proinsulin was found to be associated with a greater increase in cardiovascular events in comparison with elevated human insulin, suggesting that thromboembolic mechanisms had been activated [15].…”
Section: Discussionmentioning
confidence: 99%